Beef Cow Leasing Arrangements - Fausett, Marvin R.; Dhuyvetter, Kevin C. (My University, 1995)
This publication examines the advantages and disadvantages of beef cow share lease agreements.
MF2163_1995_11
Keywords: MF2163; Livestock; Economics; MF